HUBUNGAN FAKTOR KONDISI SANITASI LINGKUNGAN DAN PERSONAL HYGIENE DENGAN GEJALA SKABIES DI PONDOK PESANTREN DARUL HIKAM KECAMATAN RIMBO ULU KABUPATEN TEBO TAHUN 2021 - Indriani, Friska; Guspianto, Guspianto; Putri, Fitria Eka (Scientific Of Environmental Health and Diseases, 2021)
ABSTRACT Scabies is a skin disease caused by Sarcoptes scabei Var hominis. This disease commonly occurs in tropical countries with densely populated areas and low economic conditions. This study aims to determine the relationship between environmental sanitation conditions and personal hygiene factors towards the symptoms of scabies in Darul Hikam Islamic Boarding School, Rimbo Ulu Sub-district, Tebo District. This observational study used a cross-sectional design. This study used an observational method with a cross-sectional design, population as many as 400 respondents and sample as many as 63 respondents taken by proportionate strafied random sampling. The results of this study showed that 71.4% of respondents experienced symptoms of scabies; 93.7% of the respondent provided clean water facilities that met the requirements; 66.7% of residential density did not meet the requirements; 50.8% of the ventilation area did not meet the requirements; 71.4% of the respondent showed poor skin hygiene; 61.9% of the respondent showed poor towel hygiene; and 55.6% of the respondent showed poor mattress and bed sheet hygiene. The analysis indicates a relationship between residential density (p=0.008), ventilation area (p=0.000), skin cleanliness (p=0.038), towel cleanliness (0.036), and mattress and bed sheet cleanliness (p=0.049) with symptoms of scabies at Darul Hikam Islamic Boarding School. Residential density, ventilation area, skin cleanliness, towel cleanliness, and mattress and bed sheet cleanliness are related to scabies symptoms, while the provision of clean water facilities is not related. Keywords : Symptoms of scabies, Environmental Sanitation, Personal Hygiene ABSTRAK Skabies adalah penyakit kulit yang disebabkan oleh Sarcoptes scabei Var hominis. Skabies rentan terjadi di negara beriklim tropis, daerah padat penduduk dan ekonomi rendah. Penelitian ini bertujuan untuk mengetahui hubungan faktor kondisi sanitasi lingkungan dan personal hygiene terhadap gejala skabies di Pondok Pesantren Darul Hikam Kecamatan Rimbo Ulu Kabupaten Tebo. Metode penelitian dengan desain Cross Sectional, Populasi sebanyak 400 responden dan sampel sebanyak 63 responden diambil dengan teknik Proporsionate Strafied Random Sampling. Teknik analisis data dengan menggunakan uji statistik chi-square. Hasil Penelitian didapatkan terdapat 71,4% responden mengalami gejala skabies, 93,7% penyediaan sarana air bersih yang memenuhi syarat, 66,7% kepdatan hunnian yang tidak memenuhi syarat, 50,8% luas ventilasi yang tidak memenuhi syarat, 71,4% kebersihan kulit yang buruk, 61,9% kebersihan handuk yang buruk dan 55,6% kebersihan kasur dan sprei yang buruk, ada hubungan antara kepadatan hunian (p=0,008) luas ventilasi (p=0,000) kebersihan kulit (p=0,038) kebersihan handuk (0,036) dan kebersihan kasur dan seprei (p=0,049) dengan gejala skabies di Pondok Pesantren Darul Hikam. Kepadatan hunian, luas ventilasi, kebersihan kulit, kebersihan handuk, kebersihan kasur dan sprei, berhubungan dengan gejala skabies sedangkan penyediaan sarana air bersih tidak berhubungan. Kata kunci: Gejala skabies, Sanitasi Lingkungan, Personal Hygiene